Challenges in selecting humanities and social science journal articles for bibliometric analysis at University level in Sri Lanka - Navaneethakrishnan, S.; Weerasooriya, W.A. (13th Annual Research Symposium of University of Kelaniya, 2012)
The century we live in is witnessing a huge disparity between the developed countries and the developing countries. This is also true in creating knowledge. The disparity is especially clear between pure sciences and social sciences. Even with the research studies of the humanities and social sciences and their disciplines done to date, the amount of investigation is considerably smaller than in science and technology. Bibliometrics is built to provide an objective approach to assess research outputs of an individual scholar, a research agency, a university or a nation. Based on such outcomes, research funding is allocated; the reputation or credentials of a scholar or an institution are assessed. Although bibliometric assessment has been continuously criticized and improved over time for multi-dimensional measurement, reflecting more accurately the reality of research activities, it has some significant limitations when applied to the fields of humanities and social sciences. The aim of this paper is to demonstrate the methodological challenges faced in in selecting humanities and social science journal articles for bibliometric analysis at University level in Sri Lankan perspective. Based on the descriptive analysis of the problems encountered during the selection of humanities and social science journal articles for bibliometric analysis at University level in Sri Lanka, this research paper provide a basic understanding to a researcher and formulate guiding principles for them when dealing with bibliometric analysis of Humanities and Social science subjects. Variations in citation patterns, discrepancies due to journals with dual volume-numbering systems or combined volumes, publication gaps due to the war situation, language and regional bias, need of fine-grained delineation at the level of individual articles, defining the Journal coverage in the field of humanities and social sciences and unavailability of soft form of the printed journal articles are identified as the major challenges in selecting humanities and social science journal articles for bibliometric analysis at University level in Sri Lanka Even though the methodological challenges has been pointed out, responding to these challenges and designing strategies with criteria is necessary to promote a better application of bibliometrics for the evaluation of these journal articles. It paved the way for more cautious and sophisticated evaluation systems, rooted in a better understanding of the dynamics of humanities and social science journal articles for bibliometric analysis at University level in Sri Lanka one cannot deny the importance of bibliometrics remaining a useful tool and making a positive contribution to the assessment of research output.
Keywords: Library science; Bibliometrics; Research assessment; Humanities; Social sciences